Asphalt mixture added with waste battery powder and preparation method thereof
By adding waste battery powder to the asphalt mixture and modifying the matrix asphalt with its porous structure and ZnO components, the problem of insufficient performance of traditional asphalt pavement at extreme temperatures is solved, and efficient and economical performance improvement of the asphalt mixture is achieved .
Patent Information
- Application Number
- CN202411553024.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-07
AI Technical Summary
Traditional asphalt pavement shows softening, slitting and cracking in high and low temperature environments, and has weak resistance to water, oil and UV radiation, which increases maintenance costs and creates pressure on the environment. At the same time, existing high-performance bituminous mixtures rely on expensive modified bituminous, have high production costs, and their performance under extreme temperature conditions still have limitations.
By adding waste battery powder to the asphalt mixture, the matrix asphalt is modified using its porous structure and ZnO components, the resistance to rut, cracking, water loss and fatigue resistance of the asphalt mixture is improved, and at the same time, the waste battery powder is improved Utilization, simplify the modification process.
Without using modified asphalt, the road performance of the asphalt mixture is significantly improved, meets the use needs in high- and low-temperature environments, reduces production costs, and improves the utilization rate of used battery powder.
Smart Images

Figure CN119390388A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road engineering materials, and in particular to an asphalt mixture added with waste battery powder and a preparation method thereof. Background Art
[0002] With the rapid development of the transportation industry, traffic volume has increased dramatically, and vehicle loads have also increased, which has put forward more stringent requirements on the durability and stability of road engineering materials. Traditional asphalt pavements are unable to cope with the above challenges. The main manifestation is that in high temperature environments, asphalt is easy to soften, causing rutting and shifting, which greatly threatens driving safety and riding comfort; under low temperature conditions, it is easy to crack, affecting the flatness and service life of the road surface. In addition, the traditional asphalt pavement is relatively weak in resistance to water, oil and ultraviolet radiation, which makes the road surface easy to age under long-term exposure to the natural environment, which not only increases the cost of repair and maintenance, but also brings additional pressure to the environment.
[0003] In order to meet the above challenges, the industry generally adopts the method of modifying the base asphalt, and prepares high-performance modified asphalt by introducing modifiers such as rubber, resin, high molecular polymer and rubber powder. After the above modified asphalt is mixed with aggregate and mineral powder, the obtained asphalt mixture has significant improvements in high-temperature rutting resistance, low-temperature cracking resistance and weather resistance. However, the above high-performance asphalt mixture usually relies on expensive modified asphalt, which easily increases production costs. In addition, even when using high-performance modified asphalt, the performance of the asphalt mixture under certain extreme temperature conditions (especially high temperature environment) may still not meet actual needs, showing certain limitations.
[0004] In recent years, with the rapid development of my country's economy, the use of batteries has also increased year by year, and the problem of recycling and reuse of waste batteries has followed. The conventional treatment method is generally to extract valuable metals such as lithium, cobalt, nickel, zinc, copper and aluminum from waste batteries through physical disassembly, chemical treatment (hydrometallurgy, pyrometallurgy, etc.) and re-apply them to lithium batteries and energy storage equipment, forming an economic model of recycling. However, the above recycling technology has the defects of complex process and easy pollution to the environment during the recycling process.
[0005] In order to overcome the above defects, a Chinese invention patent with publication number CN 111978748 A discloses a new type of green and environmentally friendly composite modified asphalt for waste batteries, which directly utilizes waste battery powder to modify the base asphalt, thereby improving the high temperature stability and storage stability of the base asphalt while simplifying the waste battery recycling process. However, the above modification method requires the use of multiple raw materials such as cyclodextrin polymers and polystyrene, which makes the modification process complicated. In addition, the amount of waste battery powder used in the above modification method is extremely small, and the utilization rate of the waste battery powder is low. Summary of the invention
[0006] One of the purposes of the present invention is to propose an asphalt mixture with added waste battery powder, and to apply the waste battery powder to the asphalt mixture, so as to improve the road performance of the asphalt mixture without using modified asphalt and improving the utilization rate of the waste battery powder, so as to overcome the shortcomings of the prior art.
[0007] The second purpose of the present invention is to propose a method for preparing an asphalt mixture with waste battery powder added. The preparation method is simple and easy to operate, which is beneficial to avoid weakening the relevant properties of the asphalt mixture during the preparation process and improve the utilization rate of the waste battery powder.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] An asphalt mixture with waste battery powder added, which comprises 4 to 6 parts of base asphalt, 2 to 5 parts of waste battery powder and 90 to 110 parts of mixed aggregate, calculated by weight.
[0010] Wherein, calculated by weight, the mixed aggregate includes 22 to 26 parts of first coarse aggregate of 10 to 15 mm, 16 to 20 parts of second coarse aggregate of 5 to 10 mm, 19 to 23 parts of third coarse aggregate of 3 to 5 mm, and 31 to 35 parts of fine aggregate of 0 to 3 mm;
[0011] The waste battery powder has a porous structure, and the porous structure accounts for 70-80% of the waste battery powder according to volume ratio;
[0012] The chemical composition of the waste battery powder includes ZnO;
[0013] The preparation method of the waste battery powder is: disassembling the waste batteries after discharging, removing the battery shells, and crushing the battery cores.
[0014] Furthermore, the particle size of the waste battery powder is ≤750nm.
[0015] Furthermore, the waste battery powder is a solid powder obtained by crushing waste alkaline zinc-manganese batteries, and calculated by mass percentage, the chemical composition of the waste battery powder includes ZnO 25-30%, MnO2 25-30% and C 40-50%.
[0016] Furthermore, the apparent relative density of the waste battery powder is ≥2.50 g / cm 3 , moisture content ≤1%, hydrophilic coefficient <1, plasticity index <4.
[0017] Furthermore, the base asphalt is No. 70 asphalt.
[0018] Furthermore, calculated by mass ratio, the mass ratio of the matrix asphalt to the mixed aggregate is (4.5-5.5):100.
[0019] Furthermore, the raw materials of the asphalt mixture also include fibers;
[0020] Calculated by mass, the asphalt mixture includes 4 to 6 parts of base asphalt, 2 to 5 parts of waste battery powder, 1 to 3 parts of fiber and 95 to 105 parts of mixed aggregate.
[0021] Furthermore, the fiber is lignin fiber.
[0022] A method for preparing an asphalt mixture with waste battery powder added thereto, for preparing the asphalt mixture with waste battery powder added thereto, comprising the following steps:
[0023] A. Preheating the matrix asphalt, waste battery powder, mixed aggregate and lignin fiber respectively;
[0024] B. mixing the preheated mixed aggregate and the preheated matrix asphalt, and stirring to obtain a first mixed aggregate;
[0025] C. adding the preheated lignin fiber to the first mixed aggregate and stirring to obtain a second mixed aggregate;
[0026] D. Add the preheated waste battery powder into the second mixed aggregate and stir to obtain an asphalt mixture with waste battery powder added.
[0027] Furthermore, in step A, the preheating temperature is 155-165° C., and the preheating time is 0.5-1 h;
[0028] The stirring time of step B is 60 to 90 seconds; the stirring temperature of steps B, C and D is 190 to 195° C., and the total stirring time of steps B, C and D is not less than 4 minutes.
[0029] The technical solution provided by the present invention may include the following beneficial effects:
[0030] 1. Without using modified asphalt, this technical solution improves the adsorption and anchoring effect between the raw materials in the formula based on the porous structure of waste battery powder, the modification effect of ZnO in waste battery powder on the matrix asphalt, and the filling effect of waste battery powder itself on the voids in the asphalt mixture. The above-mentioned multi-faceted effects cooperate with each other, thereby improving the excellent road performance of asphalt mixture such as anti-rutting, anti-cracking, anti-water damage and anti-fatigue performance, and meeting actual use requirements. At the same time, the waste battery powder used in this technical solution can be used not only as a modifier, but also as a filler, which greatly improves the utilization rate of waste battery powder. In addition, compared with the prior art that uses waste battery powder to modify the matrix asphalt, which requires a variety of raw materials, the raw materials used in this technical solution are greatly reduced, which is conducive to simplifying the modification process.
[0031] 2. This technical solution controls the proportion of porous structure in waste battery powder to reach 70-80%, thereby greatly increasing the contact area and mechanical bite points between the raw materials in the formula, thereby significantly enhancing the adsorption and anchoring effect between the raw materials in the formula and ensuring the performance of asphalt mixture. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a scanning electron microscope image of waste battery powder in an asphalt mixture added with waste battery powder and a preparation method thereof of the present invention. DETAILED DESCRIPTION
[0033] The technical solution provides an asphalt mixture with waste battery powder added, which includes 4 to 6 parts of base asphalt, 2 to 5 parts of waste battery powder and 90 to 110 parts of mixed aggregate according to the weight percentage;
[0034] Wherein, calculated by weight, the mixed aggregate includes 22 to 26 parts of first coarse aggregate of 10 to 15 mm, 16 to 20 parts of second coarse aggregate of 5 to 10 mm, 19 to 23 parts of third coarse aggregate of 3 to 5 mm, and 31 to 35 parts of fine aggregate of 0 to 3 mm;
[0035] The waste battery powder has a porous structure, and the porous structure accounts for 70-80% of the waste battery powder according to volume ratio;
[0036] The chemical composition of the waste battery powder includes ZnO;
[0037] The preparation method of the waste battery powder is: disassembling the waste batteries after discharging, removing the battery shells, and crushing the battery cores.
[0038] In order to solve the technical problems in the prior art of increasing costs due to the reliance on high-priced modified asphalt to improve the performance of asphalt mixtures and the low recycling rate of waste battery powder, this technical solution applies waste battery powder to asphalt mixtures through the design of the asphalt mixture ratio and the optimization of raw materials. This improves the road performance of asphalt mixtures without using modified asphalt and increasing the utilization rate of waste battery powder.
[0039] Specifically, in the prior art, asphalt mixtures usually include limestone powder and slag powder as fillers, which are used to fill and enhance the adhesion between asphalt and aggregate, thereby improving the density and stability of the asphalt mixture. However, although the fillers in the prior art can improve the water damage resistance and durability of the asphalt mixture to a certain extent, the effect is relatively limited, and high-performance asphalt mixtures can usually be obtained by combining with high-performance modified asphalt, which is not conducive to reducing costs. Therefore, the present technical solution cannot be designed based on this principle.
[0040] In this technical solution, waste battery powder is used to replace filler. Among them, the waste battery powder has a porous structure (see the specific structure for details). Figure 1 As shown), the porous structure mentioned above enhances the adsorption and anchoring between the raw materials in the formula, which is conducive to forming a stable asphalt phase structure, thereby significantly improving the road performance and durability of the asphalt mixture, such as anti-rutting, anti-cracking, anti-water damage and anti-fatigue. In addition, the chemical composition of the waste battery powder includes ZnO, and ZnO can modify the matrix asphalt to generate ZnO modified asphalt. The softening point, ductility and elasticity of the ZnO modified asphalt are significantly improved compared with the matrix asphalt, which is also conducive to enhancing the road performance and durability of the asphalt mixture, such as anti-rutting, anti-cracking, anti-water damage and anti-fatigue. In addition, the waste battery powder of the present technical solution can also effectively fill the voids in the asphalt mixture, improve the density of the asphalt mixture, ensure the effective transfer of the load in the asphalt mixture, and improve the bearing capacity and durability of the asphalt mixture. That is, without using modified asphalt, this technical solution improves the adsorption and anchoring effect between the raw materials in the formula based on the porous structure of waste battery powder, the modification effect of ZnO in waste battery powder on the matrix asphalt, and the filling effect of waste battery powder itself on the voids in the asphalt mixture. The above-mentioned multi-faceted effects cooperate with each other, thereby improving the excellent road performance of asphalt mixture such as anti-rutting, anti-cracking, anti-water damage and anti-fatigue performance, and meeting actual use requirements. At the same time, the waste battery powder used in this technical solution can be used not only as a modifier, but also as a filler, which greatly improves the utilization rate of waste battery powder. In addition, compared with the prior art that uses waste battery powder to modify the matrix asphalt, which requires a variety of raw materials, the raw materials used in this technical solution are greatly reduced, which is conducive to simplifying the modification process.
[0041] Since the road performance and durability of asphalt mixtures such as anti-rutting, anti-cracking, anti-water damage and anti-fatigue are greatly affected by the porous structure in waste battery powder, when waste battery powder with insufficient porosity is used, it will affect the adsorption and anchoring between the raw materials in the formula, and it is impossible to obtain a stable asphalt phase structure. Therefore, this technical solution controls the proportion of porous structures in waste battery powders to make the proportion of porous structures in waste battery powders reach 70-80%, thereby greatly increasing the contact area and mechanical bite points between the raw materials in the formula, thereby significantly enhancing the adsorption and anchoring effect between the raw materials in the formula and ensuring the performance of asphalt mixtures.
[0042] Furthermore, in the prior art, waste battery powder is generally obtained by disassembling the waste battery after discharge to obtain the positive electrode sheet or the negative electrode sheet, and then crushing the positive electrode sheet or the negative electrode sheet. That is, the existing waste battery powder can generally only utilize the positive electrode sheet or the negative electrode sheet, and the recycling of waste batteries is limited.
[0043] In this technical solution, the waste batteries are disassembled after discharge, the battery shells are removed, and the battery cores are crushed to obtain waste battery powder. That is, this technical solution can not only utilize the positive and negative electrodes of the waste batteries, but also utilize other components such as the battery collector and diaphragm, thereby greatly improving the utilization rate of waste batteries and achieving maximum utilization of resources.
[0044] In the present technical solution, the asphalt mixture also includes mixed aggregate, which includes a first coarse aggregate of 10 to 15 mm, a second coarse aggregate of 5 to 10 mm, a third coarse aggregate of 3 to 5 mm and a fine aggregate of 0 to 3 mm. The coarse aggregate and the fine aggregate in the mixed aggregate constitute the key to the skeleton structure. The coarse aggregates are interlocked and squeezed to form the skeleton of the asphalt mixture, providing support for the asphalt mixture. The fine aggregate can fill the skeleton to ensure the strength and stability of the skeleton structure. At the same time, the surface of the coarse aggregate is rough and dry, and has a low water absorption rate, which is conducive to increasing its adhesion to the matrix asphalt, ensuring the strength of the asphalt mixture, and thus ensuring its road performance.
[0045] Furthermore, according to the weight percentage, the mixed aggregate includes 22-26 parts of the first coarse aggregate of 10-15 mm, 16-20 parts of the second coarse aggregate of 5-10 mm, 19-23 parts of the third coarse aggregate of 3-5 mm, and 31-35 parts of the fine aggregate of 0-3 mm. Aggregates of different particle sizes in the mixed aggregate can cooperate with each other to form a more compact stacking structure, reduce the void ratio in the asphalt mixture, and improve the density of the asphalt mixture, which is conducive to enhancing the road performance and durability of the asphalt mixture, such as water damage resistance, rutting resistance, crack resistance, and fatigue resistance.
[0046] It is further specified that the particle size of the waste battery powder is ≤750nm.
[0047] By optimizing the particle size of waste battery powder, on the one hand, it is beneficial to improve its utilization rate, and on the other hand, it is more conducive to utilizing its modification effect on the matrix asphalt and filling effect on the voids in the asphalt mixture, thereby improving the performance of the asphalt mixture. In addition, waste battery powder with a particle size of ≤750nm can not only be more evenly dispersed in the matrix asphalt, reduce the agglomeration phenomenon between particles, and improve the stability of the asphalt mixture, but also is more conducive to increasing its specific surface area, increasing the adsorption and anchoring between the raw materials in the formula, and is more conducive to forming a stable asphalt phase structure, thereby improving the water damage resistance, rutting resistance, cracking resistance and fatigue resistance of the asphalt mixture.
[0048] It is further explained that the waste battery powder is a solid powder obtained by crushing waste alkaline zinc-manganese batteries, and calculated by mass percentage, the chemical composition of the waste battery powder includes ZnO 25-30%, MnO2 25-30% and C 40-50%.
[0049] Since the solid powder obtained after crushing the waste alkaline zinc-manganese battery does not contain heavy metals, the environmental protection of the asphalt mixture is ensured. In addition, the technical solution preferably adds waste battery powder with a ZnO content of 25-30% calculated by mass percentage to the asphalt mixture formula, which helps to increase the ZnO content in the formula, so as to improve the water damage resistance, rutting resistance, cracking resistance and fatigue resistance of the asphalt mixture.
[0050] Further, the apparent relative density of the waste battery powder is ≥2.50 g / cm 3 , moisture content ≤1%, hydrophilic coefficient <1, plasticity index <4.
[0051] This technical solution further optimizes the apparent relative density, water content hydrophilicity coefficient and plasticity index of waste battery powder, which is conducive to improving its modification ability on matrix asphalt and the cohesion of the mortar formed by it and matrix asphalt, thereby more effectively enhancing the strength of asphalt mixture. It should be noted that the apparent relative density refers to the ratio of the mass of the material to its apparent volume (i.e., the actual volume plus the closed pore volume).
[0052] It is further specified that the base asphalt is No. 70 asphalt.
[0053] Since No. 70 asphalt has good fluidity, thermal stability, long-lasting adhesion, elasticity and water resistance, the present technical solution preferably uses No. 70 asphalt as the base asphalt to add to the formula, which is beneficial to improving the performance of the asphalt mixture.
[0054] It should be noted that the manufacturer of No. 70 base asphalt is China Petroleum Liaohe Petrochemical Branch, and the model is AH-70# petroleum asphalt.
[0055] Further explanation: calculated according to the mass ratio, the mass ratio of the base asphalt to the mixed aggregate is (4.5-5.5):100.
[0056] If the mass ratio of matrix asphalt to mixed aggregate is too large, the amount of matrix asphalt will be too much, making the asphalt mixture too soft at high temperature, thereby reducing its ability to resist deformation such as rutting and pushing; if the mass ratio of matrix asphalt to mixed aggregate is too small, the content of matrix asphalt will be too low, which will affect the bonding force between matrix asphalt and mixed aggregate. Insufficient bonding force will cause the asphalt mixture to become loose and peel off easily when subjected to load, thereby reducing the durability and service life of the asphalt pavement paved with the asphalt mixture. Therefore, the technical solution limits the mass ratio of matrix asphalt to mixed aggregate to (4.5-5.5):100, which not only ensures the high temperature stability of the asphalt mixture, but also ensures that it has good bonding force and durability, so that the asphalt mixture can adapt to various climatic conditions and usage requirements.
[0057] It is further explained that the raw materials of the asphalt mixture also include fibers;
[0058] Calculated by mass, the asphalt mixture includes 4 to 6 parts of base asphalt, 2 to 5 parts of waste battery powder, 1 to 3 parts of fiber and 95 to 105 parts of mixed aggregate.
[0059] Since fiber reinforcement has the functions of reinforcement, toughening and bridging, it can significantly improve the strength, stiffness and viscosity of asphalt mixture, thereby significantly improving the road performance and durability of asphalt pavement paved with asphalt mixture, such as anti-rutting, anti-cracking, anti-water damage and anti-fatigue.
[0060] It is further specified that the fiber is lignin fiber.
[0061] The preferred fiber of the present technical solution is wood fiber. Lignin fiber can be stably dispersed in asphalt to form a three-dimensional network structure. The above structure is conducive to effectively binding the matrix asphalt to prevent it from flowing at high temperature, thereby enhancing the high temperature stability of the asphalt mixture. In addition, lignin fiber has excellent water absorption and can absorb and store part of the water to form a tiny water film. The above water film can slow down the erosion of water on the asphalt binder, thereby improving the asphalt mixture's ability to resist water damage.
[0062] A method for preparing an asphalt mixture with waste battery powder added thereto, for preparing the asphalt mixture with waste battery powder added thereto, comprising the following steps:
[0063] A. Preheating the matrix asphalt, waste battery powder, mixed aggregate and lignin fiber respectively;
[0064] B. mixing the preheated mixed aggregate and the preheated matrix asphalt, and stirring to obtain a first mixed aggregate;
[0065] C. adding the preheated lignin fiber to the first mixed aggregate and stirring to obtain a second mixed aggregate;
[0066] D. Add the preheated waste battery powder into the second mixed aggregate and stir to obtain an asphalt mixture with waste battery powder added.
[0067] The technical solution proposes a method for preparing an asphalt mixture with waste battery powder added. The preparation method is simple and easy to operate, which is beneficial to avoid weakening the relevant properties of the asphalt mixture during the preparation process and improve the utilization rate of the waste battery powder.
[0068] Specifically, preheating the raw materials in step A is beneficial to reducing heat loss caused by temperature differences in the subsequent mixing process, improving mixing efficiency, and ensuring that all raw materials are at a similar temperature during mixing, thereby facilitating full fusion between the raw materials, ensuring the adhesion of the matrix asphalt to other raw materials, allowing the asphalt mixture to bond into a whole, and ensuring the relevant performance of the asphalt mixture.
[0069] Further, in step A, the preheating temperature is 155-165° C., and the preheating time is 0.5-1 h;
[0070] The stirring time of step B is 60 to 90 seconds; the stirring temperature of steps B, C and D is 190 to 195° C., and the total stirring time of steps B, C and D is not less than 4 minutes.
[0071] By optimizing the preheating temperature and preheating time, the stability of each raw material in the asphalt mixture is ensured, which is beneficial to improving the adhesion of the base asphalt to other raw materials and improving the relevant performance of the asphalt mixture.
[0072] Furthermore, by limiting the stirring time of step B, the coarse aggregate and fine aggregate in the mixed aggregate are distributed more evenly, and at the same time, it is avoided that the coarse aggregate is excessively worn during the stirring process due to too long a stirring time, and the angularity and integrity are damaged, thereby weakening the adhesion with the matrix asphalt, affecting the early strength and its road performance. In addition, the stirring temperature of steps B, C and D is 190-195°C, and the total stirring time of steps B, C and D is not less than 4 minutes, which is conducive to ensuring the relevant performance of the asphalt mixture.
[0073] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0074] Example 1
[0075] In this embodiment, the asphalt mixture includes 5 parts of No. 70 asphalt, 4 parts of waste battery powder with a particle size of 500nm, 2 parts of lignin fiber and 100 parts of mixed aggregates according to the weight percentage; the mixed aggregate includes 24 parts of limestone with a diameter of 10-15mm, 18 parts of limestone with a diameter of 5-10mm, 20 parts of limestone with a diameter of 3-5mm and 32 parts of limestone with a diameter of 0-3mm according to the weight percentage; wherein the waste battery powder has a porous structure, and according to the volume ratio, the porous structure accounts for 70% of the waste battery powder; the preparation method of the waste battery powder is: disassembling the waste alkaline zinc-manganese battery after discharging, removing the battery shell, and crushing the battery core; according to the weight percentage, the chemical composition of the waste battery powder includes ZnO 28%, MnO2 28% and C 44%; the apparent relative density of the waste battery powder is 2.60g / cm 3 , water content is 0.9%, hydrophilic coefficient is 0.8, and plasticity index is 3.
[0076] In this embodiment, a method for preparing an asphalt mixture with waste battery powder added comprises the following steps:
[0077] A. Preheat the matrix asphalt, waste battery powder, mixed aggregate and lignin fiber at 160 °C for 0.8 h respectively;
[0078] B. Mixing the preheated mixed aggregate and the preheated matrix asphalt, and stirring for 60 seconds to obtain the first mixed aggregate;
[0079] C. adding the preheated lignin fiber to the first mixed aggregate and stirring to obtain a second mixed aggregate;
[0080] D. Add the preheated waste battery powder to the second mixed aggregate and stir to obtain an asphalt mixture with waste battery powder added; wherein the stirring temperature of steps B, C and D is 190° C., and the total stirring time of steps B, C and D is 4 min.
[0081] Example 2
[0082] In this embodiment, the asphalt mixture includes 4 parts of No. 70 asphalt, 3 parts of waste battery powder with a particle size of 700nm, 2 parts of lignin fiber and 95 parts of mixed aggregates according to the weight percentage; the mixed aggregate includes 24 parts of limestone with a diameter of 10-15mm, 18 parts of limestone with a diameter of 5-10mm, 22 parts of limestone with a diameter of 3-5mm and 32 parts of limestone with a diameter of 0-3mm according to the weight percentage; wherein the waste battery powder has a porous structure, and according to the volume ratio, the porous structure accounts for 75% of the waste battery powder; the preparation method of the waste battery powder is: disassembling the waste alkaline zinc-manganese battery after discharging, removing the battery shell, and crushing the battery core; according to the weight percentage, the chemical composition of the waste battery powder includes ZnO 25%, MnO2 30% and C 45%; the apparent relative density of the waste battery powder is 2.8g / cm 3 , the water content is 0.8%, the hydrophilic coefficient is 0.7, and the plasticity index is 3.5.
[0083] In this embodiment, a method for preparing an asphalt mixture with waste battery powder added comprises the following steps:
[0084] A. Preheat the matrix asphalt, waste battery powder, mixed aggregate and lignin fiber at 165 °C for 0.5 h respectively;
[0085] B. Mixing the preheated mixed aggregate and the preheated matrix asphalt, and stirring for 80 seconds to obtain the first mixed aggregate;
[0086] C. adding the preheated lignin fiber to the first mixed aggregate and stirring to obtain a second mixed aggregate;
[0087] D. Add the preheated waste battery powder to the second mixed aggregate and stir to obtain an asphalt mixture with waste battery powder added; wherein the stirring temperature of steps B, C and D is 195° C., and the total stirring time of steps B, C and D is 5 min.
[0088] Example 3
[0089] In this embodiment, the asphalt mixture includes 5.5 parts of No. 70 asphalt, 5 parts of waste battery powder with a particle size of 600nm, 2 parts of lignin fiber and 105 parts of mixed aggregates according to the weight percentage; the mixed aggregate includes 24 parts of limestone with a size of 10-15mm, 20 parts of limestone with a size of 5-10mm, 23 parts of limestone with a size of 3-5mm and 33 parts of limestone with a size of 0-3mm according to the weight percentage; wherein the waste battery powder has a porous structure, and according to the volume ratio, the porous structure accounts for 80% of the waste battery powder; the preparation method of the waste battery powder is: disassembling the waste alkaline zinc-manganese battery after discharging, removing the battery shell, and crushing the battery core; according to the weight percentage, the chemical composition of the waste battery powder includes ZnO 30%, MnO2 28% and C 42%; the apparent relative density of the waste battery powder is ≥2.50g / cm 3 , moisture content ≤1%, hydrophilic coefficient <1, plasticity index <4.
[0090] In this embodiment, a method for preparing an asphalt mixture with waste battery powder added comprises the following steps:
[0091] A. Preheat the matrix asphalt, waste battery powder, mixed aggregate and lignin fiber at 155 °C for 1 h respectively;
[0092] B. Mixing the preheated mixed aggregate and the preheated matrix asphalt, and stirring for 90 seconds to obtain the first mixed aggregate;
[0093] C. adding the preheated lignin fiber to the first mixed aggregate and stirring to obtain a second mixed aggregate;
[0094] D. Add the preheated waste battery powder to the second mixed aggregate and stir to obtain an asphalt mixture with waste battery powder added; wherein the stirring temperature of steps B, C and D is 190° C., and the total stirring time of steps B, C and D is 4.5 min.
[0095] Comparative Example 1
[0096] Comparative Example 1 has the same preparation method and raw materials as Example 1, except that the asphalt mixture formula in Comparative Example 1 adopts conventional asphalt mixture prepared by modified asphalt. That is, calculated by weight, the asphalt mixture includes 4 parts of modified asphalt, 3 parts of limestone powder, 2 parts of lignin fiber and 95 parts of mixed aggregate, and the modified asphalt has a 60°C dynamic viscosity of 150,000 Pa·s, a softening point of 90°C, and an elastic recovery of 99% at 25°C.
[0097] Comparative Example 2
[0098] The preparation method and raw materials of Comparative Example 2 are the same as those of Example 1, except that no waste battery powder is added in Comparative Example 2.
[0099] Comparative Example 3
[0100] The preparation method and raw materials of Comparative Example 3 are the same as those of Example 1, except that the proportion of porous structures in the waste battery powder in Comparative Example 2 is 55%.
[0101] The asphalt mixtures of Examples 1-3 and Comparative Examples 1-3 were used to lay asphalt pavements, and the paved asphalt pavements were tested for relevant performance according to the standards specified in the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011). The results are shown in Table 1 below.
[0102] Table 1 Test results of relevant performance of asphalt pavement
[0103]
[0104] From the performance test results in Table 1, it can be seen that the various performances of the asphalt pavement paved by the asphalt mixture added with waste battery powder in the technical solution are better than those of the traditional asphalt pavement paved with the asphalt mixture prepared with SBS modified asphalt and limestone mineral powder. The technical solution applies waste battery powder to the asphalt mixture, and improves the road performance of the asphalt mixture without using modified asphalt and improving the utilization rate of waste battery powder.
[0105] In Comparative Example 2, since waste battery powder was not added, the performance of the obtained asphalt pavement was significantly reduced and could not meet the use requirements.
[0106] In Comparative Example 3, due to the reduced proportion of porous structures in the waste battery powder, the performance of the resulting asphalt pavement was significantly reduced and could not meet the use requirements.
[0107] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.
Claims
1. An asphalt mixture with waste battery powder added, characterized in that: Calculated by weight, it includes 4 to 6 parts of base asphalt, 2 to 5 parts of waste battery powder and 90 to 110 parts of mixed aggregate; Wherein, calculated by weight, the mixed aggregate includes 22 to 26 parts of first coarse aggregate of 10 to 15 mm, 16 to 20 parts of second coarse aggregate of 5 to 10 mm, 19 to 23 parts of third coarse aggregate of 3 to 5 mm, and 31 to 35 parts of fine aggregate of 0 to 3 mm; The waste battery powder has a porous structure, and the porous structure accounts for 70-80% of the waste battery powder according to volume ratio; The chemical composition of the waste battery powder includes ZnO; The preparation method of the waste battery powder is: disassembling the waste batteries after discharging, removing the battery shells, and crushing the battery cores.
2. The asphalt mixture containing waste battery powder according to claim 1, characterized in that: The particle size of the waste battery powder is ≤750nm.
3. The asphalt mixture containing waste battery powder according to claim 1, characterized in that: The waste battery powder is a solid powder obtained by crushing waste alkaline zinc-manganese batteries, and the chemical composition of the waste battery powder includes 25-30% ZnO, 25-30% MnO2 and 40-50% C in terms of mass percentage.
4. The asphalt mixture containing waste battery powder according to claim 1, characterized in that: The apparent relative density of the waste battery powder is ≥2.50 g / cm 3 , moisture content ≤1%, hydrophilic coefficient <1, plasticity index <4.
5. The asphalt mixture with waste battery powder added according to claim 1, characterized in that: The matrix asphalt is No. 70 asphalt.
6. The asphalt mixture with waste battery powder added according to claim 1, characterized in that: Calculated by mass ratio, the mass ratio of the matrix asphalt to the mixed aggregate is (4.5-5.5):
100.
7. The asphalt mixture with waste battery powder added according to claim 1, characterized in that: The raw materials of the asphalt mixture also include fibers; Calculated by mass, the asphalt mixture includes 4 to 6 parts of base asphalt, 2 to 5 parts of waste battery powder, 1 to 3 parts of fiber and 95 to 105 parts of mixed aggregate.
8. The asphalt mixture containing waste battery powder according to claim 7, characterized in that: The fibers are lignin fibers.
9. A method for preparing asphalt mixture with waste battery powder added, characterized in that: The method for preparing the asphalt mixture containing waste battery powder as claimed in any one of claims 7 to 8 comprises the following steps: A. Preheating the matrix asphalt, waste battery powder, mixed aggregate and lignin fiber respectively; B. mixing the preheated mixed aggregate and the preheated matrix asphalt, and stirring to obtain a first mixed aggregate; C. adding the preheated lignin fiber to the first mixed aggregate and stirring to obtain a second mixed aggregate; D. Add the preheated waste battery powder into the second mixed aggregate and stir to obtain an asphalt mixture with waste battery powder added.
10. The method for preparing asphalt mixture with waste battery powder added according to claim 9, characterized in that: In step A, the preheating temperature is 155-165° C., and the preheating time is 0.5-1 h; The stirring time of step B is 60 to 90 seconds; the stirring temperature of steps B, C and D is 190 to 195° C., and the total stirring time of steps B, C and D is not less than 4 minutes.
Citation Information
Patent Citations
Novel environment-friendly compound modified asphalt containing waste batteries and preparation method of novel environment-friendly compound modified asphalt
CN111978748A
Cited By
High-performance micro-rut asphalt modifier as well as preparation method and application thereof
CN121203273A